Acute and Sub-chronic Toxicity Studies of Combination of Physalis angulata L. (Cecendet) Extract and Methylprednisolone on Animals - Elin Yulinah Sukandar; Shiane Hanako Sheba (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To evaluate the safety of combination of Physalis angulata L. (Cecendet) extract and methylprednisolone through a single dose in mice (acute toxicity) and repeated doses within 90 days in rats (subchronic toxicity).Methods: Acute toxicity test was conducted to 2 groups of female mice by monitoring their behavior and death at 4 hours and 24 hours after cecendet adminstration. While subchronic toxicity test was conducted to 6 groups of rats as normal group, control group, and receive varoius cecendet dose. Each group was combined with methylprednisolone 5 mg/kg b.w. at first month and gradually taperred to 3.2 mg/kg b.w. at third month. Subchronic toxicity was evaluated by monitoring rats’ behavior, mortality, blood biochemistry, blood cell count, urinalysis, and organ macroscopic and histologic.Results: The study showed cecendet extracts did not affect mice behavior in single dose therapy up to 5 g/kg b.w. and had LD50 of more than 5 g/kg b.w., which was categorized as practically non-toxic. The sub-chronic toxicity study showed that up to 1 g/kg b.w. of cecendet extracts that was administered for 90 days did not cause death, was not organ toxic, did not affect blood biochemistries, blood cell count, and urinalysis.Conclusions: Cecendet extract and methylprednisolone combination was safe based on acute and sub-chronic toxicity data.Keywords: Acute toxicity, LD50, Lupus, Physalis angulata L, subchronic toxicity